Adaptation advantage to climate change impacts on road infrastructure in Africa through 2100 - Paul Chinowsky; Amy Schweikert; Niko Strzepek; Kyle Manahan; Kenneth Strzepek (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2011)
The African continent is facing the potential of a US183.6 billion liability to repair and maintain roads damaged from temperature and precipitation changes related to climate change through 2100. As detailed, the central part of the continent faces the greatest impact from climate change with countries facing an average cost of US22 million annually, if they adopt a proactive adaptation policy and a US54 million annual average, if a reactive approach is adopted. Additionally, countries face an average loss of opportunity to expand road networks from a low of 22 per cent to a high of 235 per cent in the central region.
Keywords: H54; L91; R42; R48; 330; infrastructure; climate change; roads; cost estimates; Klimaveränderung; Straße; Straßenbau; Afrika